Melacak Pluralisme Agama dalam Film “PEEKAY” - Purba, Veny; Retnasary, Maya; Indriyansyah, Yoggi (Universitas Brawijaya, 2020)
Diversity or plurality such as ethnicity, race, culture, and religion become a natural thing in the community, in particular, the diversity of religions must be accepted by society. The existence of religious group differences is a very natural thing, where the group is under their own theological and legal systems. The Peekay film is one of the films that represent the diversity of religions in India, by showing how every religion worships God, and also displays the identities of each religion, such as Hinduism, Islam, Catholic Christianity, Sikhism, and Jainism. Purpose of this research is to know and understand the menaing of plurality in Peekay movie. This study uses qualitative methods, and semiotics studies by using the semiotic theory of the two orders of signification model from Roland Barthes which interpret the signs through the stages of denotation, connotation, and myth, the paradigm used in conducting this research uses the constructivist paradigm. Data collection techniques in research carried out with documents, where researchers look for written sources, both from books, journals, research-relevant research, and the internet media. The results obtained by researchers are displaying several scenes that represent religious plurality, both with visuals and also dialogue and Voice Over contained in the PK film. Such as the scene depicting the buildings of places of worship of each religion, and the way each religion performs worship and Peekay who says that in this world there are many religions and each religion has its own Belief or God, where each of these religions has a way in doing God's commands. The diferents in Hinduism, Islam, Catholic Christianity, Sikhism, and Jainism symbol are the main core in this research.